The Influence of Brand Trust, Brand Image and Lifestyle on Buying Interest in Samsung Galaxy A Series Smartphones in National University Students - Umi Fadillah Rahmawati; elwisam elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze how much influence brand trust, brand image, and lifestyle have on purchase intention. This type of research uses descriptive quantitative methods and data analysis techniques using inferential analysis data and using primary data formed closed questionnaires to 100 respondents and assisted by using the SPSS version 23 program. To obtain results from consumer buying interest in the Samsung Galaxy A smartphone Series. The results of this study reveal that brand trust, brand image, and lifestyle variables have a positive and significant effect on purchase intention. This can be seen in the coefficient table in the regression equation Y = 0.308 X1 + 0.324 X2 + 0.280 X3. The conclusion is that the independent variable has a positive and significant influence on purchase intention.